Pelatihan Pemeriksaan Payudara Sendiri (SADARI) untuk Deteksi Dini Kanker Payudara di Gang Purnawirawan RT 2 Kelurahan Pelambuan Banjarmasin - Husnul Khatimatun Inayah; Netty Netty; Ari Widyarni; Elsi Setiandari Lely Octaviana (Jurnal Abdimas Kesehatan (JAK), 2023)
Cancer is a major health problem in the world and in Indonesia, according to the Global Burden of Cancer (Globocan) released by WHO in the Data and Information Center of the Ministry of Health on 2020, the number of deaths from cancer until 2018 continues to increase from year to year.Breast cancer prevention Effort by SADARI. Data from the Banjarmasin City Health Office in 2020 there were 98 cases of breast cancer in 2020 and 31 deaths. The target of the education is the mothers of Gang Punawirawan, Pelambuan village, Banjarmasin with a population of 250 families where 90 women are adults and there is 1 case of death due to breast cancer and many mothers and cadres do not know SADARI. The purpose of this community service is for cadres and mothers to understand and be able to carry out SADARI to remind breast cancer prevention.Targets and outcomes of this service, there is an increase in understanding and skills about breast cancer and early detection of cancer by SADARI. The outputs are Scientific Publications in Journals with ISSN/Proceedings, Youtube publications, and teaching materials in the form of dictation. The method of implementing this activity is in the form of pretest, breast cancer counseling, BSE training and posttest.The final result of the implementation of this activity is an increase in knowledge, understanding and skills about breast cancer, this can be seen from the comparison between the average pretest and posttest scores. Conclusion The understanding of cadres and mothers in Gang Purnawirawan RT 2, Pelambuan village can be increased through providing training and counseling about breast cancer and how to prevent it through SADARI.